2022
DOI: 10.21470/1678-9741-2020-0309
|View full text |Cite
|
Sign up to set email alerts
|

Propensity-Matched Analysis of Del Nido Cardioplegia in Adults Undergoing Cardiac Surgery with Prolonged Cross-Clamping Time

Abstract: Introduction There is not enough data in the literature regarding the safety and efficiency of del Nido cardioplegia in patients with prolonged cross-clamping time. This study aims to determine the efficacy and safety of del Nido cardioplegia compared to cold blood cardioplegia in patients with prolonged aortic cross-clamping time. Methods In this retrospective study, patients with an aortic cross-clamping time ≥ 90 minutes were included. One hundred consecutive adult p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Supplemental Table 4, http://links.lww.com/JCM/A545 lists the 42 studies ultimately included in this meta-analysis 15–28,30–34,36–40,43,46–48 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supplemental Table 4, http://links.lww.com/JCM/A545 lists the 42 studies ultimately included in this meta-analysis 15–28,30–34,36–40,43,46–48 …”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA search flow diagram and checklist are available in Supplemental Figure 1 Supplemental Table 4, http://links.lww.com/JCM/A545 lists the 42 studies ultimately included in this meta-analysis. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][30][31][32][33][34][36][37][38][39][40]43,[46][47][48]…”
Section: Study Selectionmentioning
confidence: 99%
“…In this case, we decided to use del Nido cardioplegia to minimize cardioplegia delivery times. Some recent studies have shown good outcomes using del Nido in a complex cardiac procedure in adult patients [ 8 – 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significant shortening of the CPB and XC times in the DNC groups compared with CBC was described in most of the analyzed studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] (Table 2). Four studies [18][19][20][21]…”
Section: Cardiopulmonary Bypass and Cross-clamp Timesmentioning
confidence: 99%